STRUKTUR PENYAJIAN TARI JEPIN SILAT DI DESA ARANG IMBUNG KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Euis Januarsi; Winda Istiandini; Ismunandar Ismunandar (Universitas Tanjungpura, 2019)
AbstractThe background of this study was the lack of information about accurate documentation in the form of Jepin Silat dance structure. This study aims to describe the motion, supporting elements, and design of the implementation of Jepin Silat dance. this study uses descriptive methods with qualitative forms and choreographic approaches. The source of the data that researches colleted is the results of interviews and the results of documenttation techniques. The technique of testing the validity of the data the researcher uses persistence of observation, triangulation of sources and techniques. Steps of data analysis techniques used in the form of data reduction, data display, and verification. There are 3 resource persons namely, Mrs Anisah (traditional art performer), Mrs Dewi Astuti (traditional art performer), and Mrs Marlinda (tradtional art performer). There are several kinds of motion, namely variance 1, variety 2, and variety 3. Supporting ements in fashion are clothes kurong, gill pattern, obi and pants. The make up used is realist make up. Musical instruments used are violin, aqordion, and segment. This dance venue can be displayed on the ground, stage or on the page. This research can be implemented in high school (SMA), in learning art and culture in class Xl.Keywords: structure of dance presentation, Jepin Silat dance